Si te dicen que caí de Juan Marsé : images du mythe d’Arachné - Benevent González, Silvina (Amaltea. Journal of Myth Criticism, 2010)
If the legendary tale of Arachné bears in itself a confrontation between two worlds and two visions of the divine law, Juan Marsé completes it, in his emblematic work Si te dicen que caí,with the mark left by the corruption that prevailed under Franco. Marsé’s universe expresse a struggle that goes beyond its own reality, as it gives another dimension to the isolation of the character who can’t get away from his closed and definite world, like a victim in the spider’s trap. Any possible escape remains, in any case, partial and vain, since the pressure exerted on the individual by the spatiotemporal context is too strong. This overwhelming strength of the power is violently felt through a coercive order and a vigilance that are sublimated by the falangist symbol which is nicknamed “the spider”. Black and insidious, it becomes a true leitmotiv which gives its full consistency to a polyphonic and vindictive narrative. Just like an arborescence, the spider’s web contaminates the whole writing space, which eventually acts as a protection against oblivion.